Electric generators based on dynamic semiconductor junctions - Xu, Ran (Nanyang Technological University, 2020)
In this dissertation, generators based on the dynamic semiconductor junctions with new mechanisms have been proposed and studied. By intermittently contacting and separating two semiconducting surfaces that possess different chemical potentials, both conduction current and displacement current have been generated, converting mechanical energy to electrical energy. Alternatively, by sliding two semiconducting electrodes against each other, direct current has been generated by coupling friction power and built-in electric field in the semiconductor junctions. The objectives of this thesis are to establish theoretical models for these generators, to develop protocol devices, and to identify the parameters affect the electrical energy generation. For the two new types of electric generators based on dynamic junctions, they are capable to generate conduction current, which has potential in high frequency applications.